Vertical Growth : How Self-Awareness Transforms Leaders and Organisations - Bunting, Michael; Lemieux, Carl (A The mindful leader book, 2023)
Learn the secrets to self-awareness, life-changing growth and happy, high-performing teams--from the bestselling author of The Mindful Leader Great leaders and teams don't know everything, and they don't get it right every time. What sets them apart is their commitment to continual learning and vertical growth. Vertical growth is about cultivating the self-awareness to see our self-defeating thoughts, assumptions and behaviours, and then consciously creating new behaviours that are aligned with our best intentions and aspirations. By embracing the deliberate practices and processes for vertical growth laid out in this book, you'll not only radically improve your leadership and personal wellbeing--you'll also foster the highest levels of trust, psychological safety, motivation, and creativity in the teams and groups you work with. You'll to discover how to: Identify when, where and how to develop new leadership behaviours to get better results Regulate your emotional responses in real time and handle the most difficult challenges with balance, wisdom and accountability Cultivate practices for self-awareness that foster lifelong internal growth and personal happiness Uncover and change the limiting assumptions and beliefs that keep you, your team and organisation locked in unproductive habits and behaviours Create practices and rituals that enable the highest levels of psychological safety, innovation and growth Filled with fascinating real-life case studies as well as practical tools and strategies, this is your handbook for mastering vertical growth in yourself, your team and your organisation.